2023
DOI: 10.1007/s00259-023-06166-8
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of [177Lu]Lu-DOTATATE in metastatic neuroendocrine neoplasms of different locations: data from the SEPTRALU study

Abstract: Background Peptide receptor radionuclide therapy (PRRT) is one of the most promising therapeutic strategies in neuroendocrine neoplasms (NENs). Nevertheless, its role in certain tumor sites remains unclear. This study sought to elucidate the efficacy and safety of [177Lu]Lu-DOTATATE in NENs with different locations and evaluate the effect of the tumor origin, bearing in mind other prognostic variables. Advanced NENs overexpressing somatostatin receptors (SSTRs) on functional imaging, of any grade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…A recent study analysing data collected in a Spanish national database, including patients treated with at least one PRRT cycle, reported that FDG PET/CT was not performed before PRRT in approximately 70% of cases. 22 When performed, FDG PET/CT was discordant with SST PET/CT in 17% of cases and concordant in approximately 10%. 22 The respondents were in favour of the use of FDG in NET G3 before curative surgery, and in NEC before curative intended surgery, underlying the role of metabolic imaging to exclude the presence of distant metastasis that might force a change of treatment strategy.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…A recent study analysing data collected in a Spanish national database, including patients treated with at least one PRRT cycle, reported that FDG PET/CT was not performed before PRRT in approximately 70% of cases. 22 When performed, FDG PET/CT was discordant with SST PET/CT in 17% of cases and concordant in approximately 10%. 22 The respondents were in favour of the use of FDG in NET G3 before curative surgery, and in NEC before curative intended surgery, underlying the role of metabolic imaging to exclude the presence of distant metastasis that might force a change of treatment strategy.…”
Section: Discussionmentioning
confidence: 92%
“…22 When performed, FDG PET/CT was discordant with SST PET/CT in 17% of cases and concordant in approximately 10%. 22 The respondents were in favour of the use of FDG in NET G3 before curative surgery, and in NEC before curative intended surgery, underlying the role of metabolic imaging to exclude the presence of distant metastasis that might force a change of treatment strategy. In clinical practice, high-grade NEN, especially if metastatic, are often studied with diagnostic CT and/or MRI alone, as it is generally sufficiently precise when metastatic disease is present and palliative treatment is about to be initiated.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…13 studies reported median PFS. This was not reached in three studies 22,24,25 and was 30.3 months (range 17–39 months) in the remaining 10 studies 7 . The median OS was not reached in six studies 7,9,13,20,24,28 and was 60.8 months (range 44–142.6 months) in the remaining five studies 15,17,19,25,28 …”
Section: Discussionmentioning
confidence: 95%
“…This was not reached in three studies 22,24,25 and was 30.3 months (range 17-39 months) in the remaining 10 studies. 7 The median OS was not reached in six studies 7,9,13,20,24,28…”
Section: Discussionmentioning
confidence: 99%